Output-Employment Relationship across Sectors: A Long- versus Short-Run Perspective - Afşin Şahin; Aysit Tansel; M. Hakan Berument (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
This paper investigates the nature of the output-employment relationship by using the Turkish quarterly data for the period from 1988 to 2008. Even if we fail to find a long-run relationship between aggregate output and total employment, there are long-run relationships for the aggregate output with non-agricultural employment and sectoral employment levels for seven of nine sectors that we consider. However, a further investigation for the output and employment relationship within a short-run perspective do not reveal statistically significant relationships for either total employment, or non-agriculture employment or the eight out of the nine sectors that we consider. Thus, it seems that sustainable growth is an essential economic agenda for employment generation concerning the sectors and that there is a longrun link but weak short run link with demand.
Keywords: C32; E24; E32; 330; output; employment; seasonal cointegration; Bruttoinlandsprodukt; Erwerbstätigkeit; Kointegration; Saisonkomponente; Türkei